dsRNA Molecules From the Tobacco Mosaic Virus p126 Gene Counteract TMV-Induced Proteome Changes at an Early Stage of Infection - Konakalla, Naga Charan; Nitin, Mukesh; Kaldis, Athanasios; Masarapu, Hema; Carpentier, Sebastien; Voloudakis, Andreas (Frontiers in Plant Science, 2021)
Exogenous application of double-stranded RNA (dsRNA) in the tobacco-Tobacco mosaic virus (TMV) pathosystem was shown previously to induce resistance against TMV providing an alternative approach to transgenesis. In the present study, we employed proteomics technology to elucidate the effect of TMV on tobacco as well as the effect of exogenous application of TMV p126 dsRNA molecules (dsRNAp126) at an early stage of the tobacco-TMV interaction. The proteome of tobacco leaf at 15 minutes post inoculation (mpi) in the presence or absence of dsRNAp126 molecules was studied. 36 tobacco proteins were differentially expressed in TMV-infected versus healthy tobacco leaf tissue. The identified main differential TMV responsive proteins were found to be involved in photosynthesis, energy metabolism, stress and defence responses. Most of the virus-induced changes in the tobacco leaf proteome were not observed in the leaves treated with dsRNAp126+TMV. The results indicated that the protein changes induced by TMV infection were counteracted by the exogenous application of dsRNAp126 molecules. Moreover, using small RNA sequencing, we showed that the exogenously applied dsRNAp126 was efficiently processed in tobacco as early as 15 minutes post application (mpa) to produce small interfering RNAs (siRNAs); the dicing pattern was not affected by the presence of TMV. The presence of dsRNAp126 reduced TMV p126 RNA abundance suggesting virus titre reduction via a sequence-specific mechanism, since a non-homologous dsRNA did not protect from TMV infection nor affected TMV accumulation.